Implementasi Persidangan Elektronik Menurut Perma No. 04 Tahun 2020 pada Perkara Pidana Khusus di PN Kupang Kelas 1A (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This study aims to determine the implementation in electronic trials, to determine the impact of technical and substantive constraints on the quality and fairness of electronic trials, to find out whether electronic trials can uphold material truth in special criminal cases of child molestation. In data collection, the authors used interviews and informants. For data analysis techniques, the author uses qualitative descriptive analysis, which in this study uses the results of interviews with six (6) informants. From the results of the study, it can be said that the implementation of electronic trials according to PERMA No. 4 of 2020 in child molestation cases is no different from child molestation trials as usual, the trial procedures are the same as those contained in the Criminal Procedure Code which are different only the location of the parties concerned. The technical obstacles faced are communication network disruption, lack of infrastructure; and lack of human resources Substantive obstacles faced in electronic trials are: relatively closed trials; difficulty of proof; and the judge's difficulty in using the judge's conviction. The impact of technical and substantive constraints is that electronic trials become longer and judges cannot be sure that the evidence presented is legitimately seized. Electronic trials can uphold material truth as the Code of Criminal Procedure was created with the aim of obtaining material truth.